Jake Tucker's potato garden in St. Philip's - Squires, Allen; Squires, Pearl (1962)
Photograph of potato garden and house with group of people identified by Pearl Squires slide label as (left to right) Little Les, Jake [Tucker], Edna [Tucker], Leslie [Squires] and Al [Squires] , and Butch the dog.